Dinuclear Tridentate Ru(II) Complex with Strong Near-Infrared Light-Triggered Anticancer Activity - Wei L.; Kushwaha R.; Sadhukhan T.; Wu H.; Dao A.; Zhang Z.; Zhu H.; Gong Q.; Ru J.; Liang C.; Zhang P.; Banerjee S.; Huang H. (My University, 2025)
The design of the dinuclear Ru(II) complex (Ru2) with strong near-infrared (NIR) absorption properties has been reported for efficient anticancer phototherapy. Under 700 nm LED light excitation, Ru2 exhibited remarkable synergistic type I/II photosensitization ability and photocatalytic activity toward intracellular biomolecules. Ru2 showed impressive 700 nm light-triggered anticancer activity under normoxia and hypoxia compared with the clinically used photosensitizer Chlorin e6. The mechanistic studies showed that Ru2 induced intracellular redox imbalance and perturbed the energy metabolism and biosynthesis in A549 cancer cells. Overall, this work provides a new strategy for developing efficient metal-based complexes for anticancer phototherapy under NIR light. © 2024 American Chemical Society.